2002
DOI: 10.1080/00207230214400
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Of Health Effects Of Air Pollution On Peasant Farmers In Benue State, Nigeria

Abstract: This paper examines the health effects due to air pollution on peasant farmers in Benue State, Nigeria. The study is based on the review of epidemiological data collected from clinics and hospitals in the State. The diseases found to be prevalent in the study area include allergic asthma, pulmonary tuberculosis, pneumonia, upper respiratory tract infection (URTI), chronic bronchitis and visual impairment. The ambient air quality in the state is far worse than national and international ambient air quality stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The health effects which are due to air pollution are called epidemiological diseases. These diseases are well-defined by Nwachukwu and Ugwuanyi (2010), and Ugwuanyi and Obi (2002). Epidemiological studies play an ever important role in environmental health risk assessment.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The health effects which are due to air pollution are called epidemiological diseases. These diseases are well-defined by Nwachukwu and Ugwuanyi (2010), and Ugwuanyi and Obi (2002). Epidemiological studies play an ever important role in environmental health risk assessment.…”
Section: Introductionmentioning
confidence: 97%
“…The human health effects due to air pollutants include carcinogenicity, pulmonary tuberculosis, cerebrospinal meningitis, pneumonia, whooping cough and measles (Nwachukwu and Ugwuanyi, 2010;Ugwuanyi and Obi, 2002); while the environmental effect is global warming (Bolion, 1991). The health effects which are due to air pollution are called epidemiological diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent studies done on the effect of air pollution and diseases associated to ambient air pollution in some Nigerian cities also revealed that sickness such as tuberculosis, cerebrospinal meningitis, pneumonia, measles, chronic bronchitis, pertussis, pulmonary, complicated coughing, sneezing and acute respiratory infection, cardiovascular diseases etc. are commonly prevalent in those cities [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…According to [25], exposure to high levels of H 2 S can cause muscle cramps, low blood pressure, slow respiration and loss of consciousness. Short-term exposure to moderate concentrations of hydrogen sulphide (between1 to 10 ppmv) will cause eye, nose, and throat irritation, nausea, dizziness, breathing problems, headaches, loss of appetite, and problems sleeping while an extended exposure will irritate breathing passages and may lead to pulmonary edema (fluid buildup in the lungs).…”
mentioning
confidence: 99%